Rapid Spontaneous Resolution of Acute Epidural Hematoma: A Case Report and Review of the Literature - Aydemir, Fatih (Balkan Med J, 2016)
BACKGROUND: Epidural hematomas (EDH) are pathologies in which the early diagnosis and treatment are important. Resolution under 24 hours is very rare. CASE REPORT: An 11-month-old male patient was brought to the emergency department with head trauma from falling out of bed onto his back. There were no neurological deficits, except for the patient being somnolent. Computed tomography (CT) of the patient revealed subgaleal edema in the right parietal region, linear fracture and image consistent with EDH with a thickness of about 9 mm underneath fracture. A control CT was performed after 3 hours as somnolence continued in follow-up of the patient. Hematoma in the epidural region was observed to completely resolve and edema in the subgaleal region was observed to gain hemorrhagic characteristics. CONCLUSION: In total, 15 cases have been reported, including our case, in the literature with resolution less than 24 hours. Our case has the fourth fastest resolution ever reported in the English literature. We think that the most important factor in the rapid spontaneous resolution is the presence of a connection between the epidural and epicranial space, either through a fracture or cranial sutures